Nilai- Nilai yang Terkandung dalam Satua Cetrung - Ni Made Ari Tresnawati (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
Balinese literature is historical evidence of Balinese society, which is one part of the national culture which is domiciled as a vehicle for cultural expression which contains aesthetic, religious, and socio-political processing of Balinese society. Satua Bali is one of the traditional Balinese literatures called oral literature. Satua is also a means of moral and character education in children that must be instilled from an early age to shape children's character. By providing indirect guidance through satua (fairy tales), the character, mentality, attitude, and behavior of the child will definitely be affected as well. This is because the aspect of the value of the unit is indeed very high, useful, and useful. Satua Cetrung is a literary work that contains noble values and can be used as a guide in life. The values contained include: religious, logical values , and ethical values.